Learning to be a primary teacher: Some perspectives from Mathematics Education (Edma 0-6: Educación Matemática en la Infancia, 2021)
Support Early Childhood and Primary prospective teachers’ development of teaching competencies implies not only identifying what teachers must come to know to develop good practices, but also thinking about the learning opportunities that training programs can offer. In this paper, we present the principles supporting the design of these opportunities in the Early Childhood and Primary teacher education programs at the University of Alicante, considering the development of professional noticing students’ mathematical thinking. We exemplify these principles through two examples of learning environments for Early Childhood Education prospective teachers focused on magnitude and measurement, and for Primary Education prospective teachers focused on fractions.
Keywords: Early Childhood Education; Primary Education; Primary teacher education; Teaching competence; Mathematics teaching; Learning to noticing; Teacher learning